2014
DOI: 10.1186/1745-6215-15-385
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention to protect the mother-infant relationship following postnatal depression: study protocol for a randomised controlled trial

Abstract: BackgroundAt least 13% of mothers experience depression in the first postnatal year, with accompanying feelings of despair and a range of debilitating symptoms. Serious sequelae include disturbances in the mother-infant relationship and poor long-term cognitive and behavioural outcomes for the child. Surprisingly, treatment of maternal symptoms of postnatal depression does not improve the mother-infant relationship for a majority of women. Targeted interventions to improve the mother-infant relationship follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 61 publications
0
19
0
1
Order By: Relevance
“…Smoking, alcohol intake, diet, and physical activity are all modifiable preconception lifestyle risk factors [1][2][3][4][5][6]. Poorer psychological well-being is associated with poorer lifestyle before and during pregnancy [7][8][9], as well as being a risk factor for postnatal mood disorders and associated complications such as poor child cognitive, physical, and behavioural outcomes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking, alcohol intake, diet, and physical activity are all modifiable preconception lifestyle risk factors [1][2][3][4][5][6]. Poorer psychological well-being is associated with poorer lifestyle before and during pregnancy [7][8][9], as well as being a risk factor for postnatal mood disorders and associated complications such as poor child cognitive, physical, and behavioural outcomes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Within recent years a few protocols for infant trials have been published [ 32 37 ], but none of these are aimed at universal or low risk populations. Given the relatively low numbers of infant program efficacy or effectiveness trials conducted in this emerging field, it is useful for researchers to learn about some of the possible measures that can be used.…”
Section: Introductionmentioning
confidence: 99%
“…Given the risk that maternal depression poses for offspring attachment security and subsequent social competence, interventions that target the early child–parent relationship may be useful for preventing maladaptive developmental trajectories. Relational interventions are of particular importance given that research has indicated that treating maternal depressive symptoms alone is not sufficient for preventing negative sequelae in offspring (Milgrom & Holt, 2014; Nylen, Moran, Franklin, & O'Hara, 2006; Tsivos, Calam, Sanders, & Wittkowski, 2015). Evidence has supported the use of attachment-based interventions for improving outcomes among high-risk infants and children (for reviews, see Berlin, Zeanah, & Lieberman, 2008; Juffer, Bakermans-Kranenburg, & van IJzendoorn, 2014; Steele et al, 2014; Zeanah, Berlin, & Boris, 2011).…”
Section: Child–parent Psychotherapy (Cpp) For the Promotion Of Offsprmentioning
confidence: 99%